Research on multipath suppression performance of multiple BOC signals of navigation satellite. Issue 1 (March 2020) - Wang, Yan; Zhao, Wei; Shen, YangHe; Yu, Su
Abstract: BOC(Binary Offset Carrier) signal is a kind of navigation satellite downlink signal. Compared with BPSK(Binary Phase Shift Keying) modulation signal, it can improve the multipath suppression performance of navigation system. BOC signal modulation includes a variety of extended signal modulation modes, including TMBOC(time-multiplexed BOC), AltBOC(Alternative BOC) signals, etc. It is an important subject to study the performance of multipath suppression of various BOC signals. In this paper, the multipath error model is constructed by using the noncoherent early-late processing track loop, the performance of multipath suppression of TD-AltBOC(Time Division Alternative BOC) and AltBOC signals for different front-end bandwidth of the receiver is analyzed. By studying the average multipath error and envelope value of AltBOC (15, 10), BOC (1, 1) and TMBOC (6, 1, 4/33) signals, the performance comparison results of three kinds of BOC modulation are given. In order to verify the research results of multipath suppression performance, the receiver is used to receive the signals of different BOC modulation systems transmitted by navigation satellite, The multipath error is obtained by the combination of dual frequency pseudo range and carrier phase. The experimental results show that AltBOC (15, 10) has the best multi-path suppression performance, followed by TMBOC (6, 1, 4/33), and BOC (1, 1) has the worst multi-path suppression performance compared with the others, which proves the correctness of the research results of multi-path suppression performance of various BOC signals.